POLITISASI PROFESI GURU OLEH PEMERINTAH DAERAH STUDI KASUS DI KABUPATEN BANYUASIN III - Shah, Khaf; Sirozi, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The politicization of the teaching profession by local governments is a phenomenon that has sparked debate in the context of education in Indonesia. This research aims to investigate the practice of politicization of the teaching profession by the Regional Government of Banyuasin III Regency. Case studies were conducted to gain an in-depth understanding of how this politicization occurs, its impact on teachers, students, and the education system as a whole, as well as the efforts made to overcome or minimize this practice. Qualitative research methods were used, including in-depth interviews with teachers, government officials, and other stakeholders, as well as analysis of policy documents and related secondary data. The research results show that the politicization of the teaching profession in Banyuasin III Regency is reflected in various aspects, ranging from teacher placement based on political affiliation to political influence in curriculum development. This has led to instability in the educational environment, inequality in educational opportunities, and a decline in the overall quality of education. However, there are efforts from a number of parties to combat the politicization of the teaching profession, including through community advocacy, developing independent teachers, and strengthening supervision mechanisms. Keywords: local government, politicization, teaching profession